mNUDC is required for plus-end-directed transport of cytoplasmic dynein and dynactins by kinesin-1 - Yamada, Masami (Nature Publishing Group, 2010)
Lissencephaly is a devastating neurological disorder caused by defective neuronal migration. The LIS1 (or PAFAH1B1) gene was identified as the gene mutated in lissencephaly patients, and was found to regulate cytoplasmic dynein function and localization. In particular, LIS1 is essential for anterograde transport of cytoplasmic dynein as a part of the cytoplasmic dynein–LIS1–microtubule complex in a kinesin-1-dependent manner. However, the underlying mechanism by which a cytoplasmic dynein–LIS1–microtubule complex binds kinesin-1 is unknown. Here, we report that mNUDC (mammalian NUDC) interacts with kinesin-1 and is required for the anterograde transport of a cytoplasmic dynein complex by kinesin-1. mNUDC is also required for anterograde transport of a dynactin-containing complex. Inhibition of mNUDC severely suppressed anterograde transport of distinct cytoplasmic dynein and dynactin complexes, whereas motility of kinesin-1 remained intact. Reconstruction experiments clearly demonstrated that mNUDC mediates the interaction of the dynein or dynactin complex with kinesin-1 and supports their transport by kinesin-1. Our findings have uncovered an essential role of mNUDC for anterograde transport of dynein and dynactin by kinesin-1.